If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + 9x = -93 Solving -12 + 9x = -93 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 9x = -93 + 12 Combine like terms: -12 + 12 = 0 0 + 9x = -93 + 12 9x = -93 + 12 Combine like terms: -93 + 12 = -81 9x = -81 Divide each side by '9'. x = -9 Simplifying x = -9
| (5t^4-10t^3)/(t^3-2t^2) | | -6w=5f | | 90lb=kg | | 1+3n+2n+8= | | 4.72f-0.5=-61.6-8.3f | | 3x-4y-72=11 | | 90lb= | | 10+5x=3x | | 1.43(19/37) | | 6x+5y=38 | | 0.75x=0.33x+15 | | 3+1-5n+2n=1-8n | | Tanx=.3 | | 2.5l= | | 12/z=2 | | 2x+6x+10-4=38 | | -12n+6(n+8)=8(-n+2) | | 19.8/1.8 | | 0.79x-24=1.19 | | t-22=4 | | 6km= | | 3/5-1/3=10/3 | | 2(x-3)-2(x-5)+2x=0 | | (x-5/2)^2=13/4 | | 1/3f=9 | | 87=7 | | 18m+42n=2 | | -6+2a+1+1+10a= | | (-1/2)y=11-3x | | 2(12+x)=24+2x | | -2m+9+24=m-6 | | 5x+19=7x |